PENERAPAN MODEL PEMBELAJARAN PRAKTIK ELEKTRONIKA ANALOG DENGAN PENDEKATAN KOOPERATIF TIPE STAD - Sabran, Sabran; Purnamawati, Purnamawati (Universitas Negeri Makassar, 2015)
This study aims to describe student activity and learning outcomeshe analog electronics of the course students practice analog electronics. This type of research is a classroom action research that consists of 2 cycles. Each cycle is carried out through four stages: planning, implementation, observation, and reflection. Data were obtained through observation and tests. Data from observation and students analyzed in terms of percentage. Data were analyzed student achievement test based on practice learning criteria. The results showed an increase in the percentage of student activity in the first cycle and second cycle. Student activity increased from 57.6% in the first cycle to 77.6% in the second cycle. Learning results obtained by students has increased. For the average grades of students also increased, namely 66.36 in Cycle I to 78.39 in Cycle II. Based on the results obtained it can be concluded that the application of the practice learning model can improve student learning outcomes.